Cytotoxic and apoptotic effects of the combination of palladium (II) 5, 5-diethylbarbiturate complex with bis(2-pyridylmethyl)amine and curcumin on non small lung cancer cell lines. Issue 5 (1st March 2017) - Tunc, Duygu; Dere, Egemen; Karakas, Didem; Cevatemre, Buse; Yilmaz, Veysel Turan; Ulukaya, Engin
Graphical abstract: Abstract: Metal-based chemotherapeutics such as cisplatin are widely used treatment of lung cancer which is the major cause of cancer-related mortality worldwide. Recent studies demonstrated that novel metal-based compounds have strong cytotoxic activity in a similar way as cisplatin. Therefore, metal-based compounds have been synthesized and investigated in order to determine their cytotoxic activities. It has been also reported curcumin, which has been derived from turmeric plant, has powerful cytotoxic effect on various cancer cell lines. In the light of these data, it has been investigated the cytotoxic effects of combination of curcumin (0.78–100 μM) and palladium (II) 5, 5-diethylbarbiturate complex with bis(2-pyridylmethyl)amine [Pd(II) complex] (0.39–50 μM) against non small lung cancer cell lines, A549 and H1299. It has been found that combination of Pd(II) complex and curcumin enhanced the cytotoxic activity and apoptotic cell death at 48 h, compared to single use of each agent, only in H1299 cell line (combination index <1). Apoptosis was evident by annexin v staining positivity, increased caspase 3/7 activity and the presence of pyknotic nuclei. Pro-apoptotic genes of TNFRSF10A and HRK were found to be involved in apoptotic cell death. In conclusion, the application of this combination may be regarded as a novel and effective approach for the treatment of lung cancer due to its promising cytotoxic and apoptotic effect.